Spin–orbit stiffness of the spin‐polarized electron gas. Issue 4 (25th February 2016) - Baboux, F.; Perez, F.; Ullrich, C. A.; Karczewski, G.; Wojtowicz, T.
Abstract : In a spin‐polarized electron gas, Coulomb interaction couples the spin and motion degrees of freedom to build propagating spin waves. The spin wave stiffness S sw quantifies the energy cost to trigger such excitation by perturbing the kinetic energy of the electron gas (i.e. putting it in motion). Here we introduce the concept of spin–orbit stiffness, S so, as the energy necessary to excite a spin wave with a spin polarization induced by spin–orbit coupling. This quantity governs the Coulombic enhancement of the spin–orbit field acting of the spin wave. First‐principles calculations and electronic Raman scattering experiments carried out on a model spin‐polarized electron gas, embedded in a CdMnTe quantum well, demonstrate that S so = S sw . Through optical gating of the structure, we demonstrate the reproducible tuning of S so by a factor of 3, highlighting the great potential of spin–orbit control of spin waves in view of spintronics applications. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : Spin–orbit coupling can be used to trigger the precession of spin‐waves. The authors investigate the energy cost of such process (the spin–orbit stiffness) in a model system, the two‐dimensional electron gas confined in a magnetic quantum well. Combined electronic Raman scattering experiments and first‐principles calculations show that remarkably, the electron gas responds identically to a kinetic or spin–orbit disturbance of its ground state.